Crohn's colitis and sarcoidosis. Issue 732 (October 1986) - McCormick, P. A.; O'Donoghue, D. P.; FitzGerald, M. X.
Abstract : We report a patient with both sarcoidosis and Crohn's colitis, an association not previously documented. We review the literature and discuss the areas of overlap in these two conditions.